Reflective Practice in Teacher Education: A Look into Past and Present Theories, and Some Pertinent Issues - Nur Rizky Alfiany Suaib (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
Many educators regard the practice of pedagogical reflection as a prime motivator in the professional growth of teachers. This idea has spurred the realization of the practice of reflection since the early stages of the university's teacher education program. Several scholars have developed their ideas regarding excellent practices in reflection throughout the years. They presented methodologies, concepts, and ways to construct the course of reflection from non-reflective to critical reflective by identifying the reflective thought process and underpinning the degrees of reflection. These ideas would also allow educators to create evaluations for reflective practice. However, this sound theoretical framework is frequently riddled with flaws that linger to the present time, particularly about the extent to which such activity will provide noteworthy growth for teachers, as well as the legitimacy of its reflexivity itself. This paper tries to revisit the origin of the concept, the development, and pinpoint the persistent issues. This, hopefully, would enable us to seek the deeper insight into the dynamics of reflective practice in teacher education program.